PENGARUH MOTIVASI MEMBAYAR PAJAK DAN TINGKAT PENDIDIKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Laksmita Ananda Putri Gulo (PT Sanagi Edu Konsultan, 2025)
This study aims to determine the effect of tax payment motivation and education level on individual taxpayer compliance at the West Jakarta Regional Office of the Directorate General of Taxes. The sample in this study was 159 individual taxpayers. The sampling technique used was incidental sampling. Data collection was conducted using a questionnaire. The test instruments were analyzed using validity and reliability tests. The prerequisite test used the classical assumption test. The data analysis technique used multiple linear regression. The results of this study indicate that tax payment motivation has a positive and significant effect on taxpayer compliance, while education level has a positive but insignificant effect on individual taxpayer compliance.